PENGEMBANGAN MODUL GEOMETRI UNTUK MENINGKATKAN PENALARAN SPASIAL MAHASISWA CALON GURU MI/SD - Fatmahanik, Ulum; Afif , Yusmicha Ulya (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research aims to produce a feasible module, to determine student responses to the module that has been developed, and to determine the improvement in students' spatial reasoning after using the module that was developed. The development model in this research uses the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model in producing products. The results of the material expert assessment show that the module that has been developed has decent and very good quality with a score of 93.3%. The results of the media expert assessment show that the module developed has decent and very good quality with a score of 87%. The results of the learning expert assessment showed that the module developed was of decent and very good quality with a score of 92%. Meanwhile, the results of the language expert's assessment showed that the module developed was of decent and very good quality with a score of 92%. The results of student responses show that what was developed was of decent and very good quality with a score of 77.5%. And the module developed is effective in improving students' spatial reasoning as shown by an n-gain score of 0.71 in the high category or 71% so that the module is in the effective category in improving spatial reasoning.